2022
DOI: 10.1038/s41598-022-08542-0
|View full text |Cite
|
Sign up to set email alerts
|

Removal of yttrium from rare-earth wastewater by Serratia marcescens: biosorption optimization and mechanisms studies

Abstract: The discharge of yttrium containing wastewater is a potential risk to human health. Although biosorption is a promising method to remove yttrium from wastewater, whereas the application of it is limited due to the lack of efficient biosorbents. In this study, the removal of yttrium from wastewater using Serratia marcescens as a biosorbent was conducted. The effects of six parameters including pH (2–5.5), initial yttrium concentration (10–110 mg/L), biosorbent dosage (0.1–0.5 g/L), biosorption time (10–700 min)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
(73 reference statements)
3
1
0
Order By: Relevance
“…In addition, metal analysis strongly indicated an ion-exchange mechanism during the biosorption process in which Na + , K + , Mg 2+ , and Ca 2+ ions are replaced by metal cations that bind to the surface of the biomass. These observations are in accordance with previous studies that were conducted on algal, bacterial, and other biomasses (Acheampong et al, 2011;Sulaymon et al, 2013;Liang and Shen 2022). The isolation of single target elements in a technical biosorption process remains a challenging task due to the complex surface structure and the heterogeneity of functional groups.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, metal analysis strongly indicated an ion-exchange mechanism during the biosorption process in which Na + , K + , Mg 2+ , and Ca 2+ ions are replaced by metal cations that bind to the surface of the biomass. These observations are in accordance with previous studies that were conducted on algal, bacterial, and other biomasses (Acheampong et al, 2011;Sulaymon et al, 2013;Liang and Shen 2022). The isolation of single target elements in a technical biosorption process remains a challenging task due to the complex surface structure and the heterogeneity of functional groups.…”
Section: Discussionsupporting
confidence: 91%
“…At pH 1, no notable metal adsorption was measured for all tested biomasses. These results are in accordance with previous studies on cyanobacteria, bacteria, and green algae regarding metal adsorption (Kuyucak and Volesky 1988;Gong et al, 2005;Lupea et al, 2012;Liang and Shen 2022).…”
Section: Figuresupporting
confidence: 93%
See 1 more Smart Citation
“…To date, no studies have reported on the biosorption capacity of the SH31 strain for rare-earth elements. However, a previous report demonstrated that Serratia marcescens can be used to biosorb Y 3+ , suggesting the involvement of hydroxyl, amine, and carboxyl groups derived from proteins and polysaccharides in metal biosorption [38]. Furthermore, the FTIR spectra of a thermophilic bacterium, Thermus scotoductus SA-01, during the biosorption of Eu 3+ , indicated that the interaction occurs mainly through phosphate, carboxyl, and carbonyl of amide groups [8].…”
Section: Discussionmentioning
confidence: 95%
“…The pH of a solution is one of the most crucial aspects of biosorption since it affects the charge and ionization of functional groups on the cell surface [22]. In general, a low pH seems to be favourable for cation binding stability due to the overall negative charge of the cell surface and increased metal solubility under acidic conditions [27,28], but depending on the metal of interest and the biosorbing organism, binding capacity might decrease under highly acidic solution pH [29]. Other factors, which could increase biosorption include elevated temperatures (increases surface activity and kinetic energy), low ionic strength (less competition of binding sites), high agitation speed (enhances pollutant removal rate by minimizing mass transfer resistance), high pollutant load, etc.…”
Section: Introductionmentioning
confidence: 99%